ANALISA KELAYAKAN USAHA PEMBUATAN NATA DE COCO MENGGUNAKAN SUMBER NITROGEN DARI KECAMBAH - Mandasari, Fika; Santosa, Budi; Rozana, Rozana (Fakultas Pertanian, 2018)
Nata de coco is a coconut based food product produced by the bacterium Acetobacter xylinum. The purpose of this study was to analyze the feasibility of business in the manufacture of nata de coco by utilizing sprouts as an alternative nitrogen source. Sprouts have a nitrogen content of 20-30%. Calculation of business feasibility analysis on the nata de coco extraction from sprouts, namely BEP Unit of 2.528 and BEP Price, namely Rp 29.330.290 for 5 years of production. The HPP is Rp 10.026,82 and the selling price is Rp 11.600 per 1000 grams. The NPV calculation is Rp 8.350.151, Net B/C is 1,6 while the R/C ratio obtained is 1,16. The IRR for the nata de coco business is 19% and the Payback Period or the time period needed to return all costs incurred in investing in nata de coco products for 1,03 years. Nata de coco merupakan produk pangan berbahan dasar air kelapa yang dihasilkan oleh bakteri Acetobacter xylinum. Tujuan dari penelitian ini adalah untuk menganalisa kelayakan usaha pada pembuatan nata de coco dengan memanfaatkan kecambah sebagai sumber nitrogen alternatif. Kecambah mempunyai kandungan nitrogen sebesar 20-30%. Perhitungan analisa kelayakan usaha pada pembutan nata de coco dari kecambah yaitu BEP Unit sebesar 2.528 dan BEP Harga yaitu Rp 29.330.290 selama 5 tahun produksi. HPP sebesar Rp 10.026,82 dan harga jual yaitu Rp 11.600 per 1000 gram. Perhitungan NPV sebesar Rp 8.350.151, Net B/C sebesar 1,6 sedangkan R/C ratio yang diperoleh sebesar 1,16. IRR pada usaha nata de coco sebesar 19% dan Payback Period atau jangka waktu yang dibutuhkan untuk mengembalikan semua biaya yang telah dikeluarkan dalam berinvestasi produk nata de coco selama 1,03 tahun.